(untitled) (Bangladesh Journal of Zoology, 2021)
Stock Assessment of Tenualosa ilisha (Hamilton, 1822) were estimated using FiSAT-II software with length-frequency data collected from different landing centers. The Southeast Coast of Bay Of Bengal, Cox’s Bazar. The Von Bertalanffy growth parameters Land K for the species were asymptotic length (L∞) was 51.41 cm, growth rate (K) was 0.75 year-1 and t0 = -0.2 year respectively. The estimated value of total mortality (Z) based on length converted catch curve using these growth parameters was 2.35 year-1.Natural mortality (M) based on growth parameters and mean environmental temperature (T = 27° C) was 1.00 year-1 and fishing mortality (F) was 1.35 year-1. Optimum length of hilsa at first capture (Lc=L50) was 28.36 cm TL. Growth performance indices (ϕ’) was 3.30. The estimated value of the exploitation rate (E) using the length-converted catch curve was 0.57. The recruitment pattern of this species was continuous and two peaks per year. The present investigation clearly showed the over fishing (E > 0.50) condition for T. ilisha in Bangladesh. The estimated length-weight relationship for the combined sex was found to be W = 0.0109 L3. Virtual population analysis (VPA) showed that the maximum fishing mortality occurring in the length between 30 to 35 cm with a maximum value in the length of 32 cm that repeatedly indicate high fishing mortality in the T. ilisha. The generalized length-weight relationship was fitted with the pooled data of all monthly samples were BW = 0.029 TL2.718 (R2= 0.833) respectively. The results revealed that all length-weight relationships were highly correlated (r > 0.993). Maximum sustainable yield (MSY) was estimated as 435,554 t. Bangladesh J. Zool. 48(2): 231-241, 2020